The Bishop's Utopia : Envisioning Improvement in Colonial Peru - Soule, Emily Berquist, 1975- (Book collections on Project MUSE., 2014)
"In December 1788, in the northern Peruvian city of Trujillo, fifty-one-year-old Spanish Bishop Baltasar Jaime Martínez Compañón stood surrounded by twenty-four large wooden crates, each numbered and marked with its final destination of Madrid. The crates contained carefully preserved zoological, botanical, and mineral specimens collected from Trujillo's steamy rainforests, agricultural valleys, rocky sierra, and coastal desert. To accompany this collection, the Bishop had also commissioned from Indian artisans nine volumes of hand-painted images portraying the people, plants, and animals of Trujillo. He imagined that the collection and the watercolors not only would contribute to his quest to study the native cultures of Northern Peru but also would supply valuable information for his plans to transform Trujillo into an orderly, profitable slice of the Spanish Empire.